An engineering approach for the prediction of fatigue damage in the part load regime. Issue 1 (1st September 2022) - Von Locquenghien, F; Leibing, B
Abstract: Due to the volatile electricity received from solar and wind power plants, the energy market requires highly variable hydropower machines which are able to cope with fast changes of their operating regimes. With the need for flexible operation, Francis runners are exposed to various operating conditions outside the traditional operating range. Hence, the runners must be specifically designed for long time part load operation to meet hydraulic and structural requirements. Therefore, it is inevitable to have a reliable but also practical engineering approach in the design phase of the projects in order to ensure sufficient fatigue life of the Francis runners. Deep part load operation mainly consists of stochastic loads acting on the runner blades. Previous publications show that it is reasonable to normalize the Rainflow matrix of stress amplitudes to represent the characteristic behaviour at deep part load operation. Hence, it is feasible to utilize the normalized Rainflow matrix to predict the fatigue damage of Francis runner designs without prototype measurements. Within this paper, a scaling method to derive project specific fatigue results for deep part load is introduced and subsequently validated through an intercomparison of available strain gauge measurement data and prediction. Based on the results, the accuracy of the proposed engineering approach and possible impacts of different boundary conditions are discussed.